Efficacy of extracts from eight economically important forestry species against grapevine downy mildew (Plasmopara viticola) and identification of active constituents. (December 2017) - Mulholland, Dulcie A.; Thuerig, Barbara; Langat, Moses K.; Tamm, Lucius; Nawrot, Dorota A.; James, Emily E.; Qayyum, Meywish; Shen, Danni; Ennis, Kallie; Jones, Amy; Hokkanen, Heikki; Demidova, Natalia; et al.
Abstract: Downy mildew caused by the oomycete Plasmopara viticola is the most devastating pathogen of grapevine. In this study, extracts of the bark of eight important northern forestry species were screened to find extracts showing activity against this pathogen and to identify the active compounds. Extracts from all eight species showed activity against P. viticola, the most promising, dichloromethane extracts of three Larix species, almost completely protecting grapevine from downy mildew under semi-controlled conditions. Five promising lead compounds were isolated: larixol, larixyl acetate, lariciresinol and lariciresinol acetate from Larix species and 7α, 15-dihydroxydehydroabietic acid from Pinus sylvestris . These compounds showed 90%–100% efficacy. Larixol and larixyl acetate or 7α, 15-dihydroxydehydroabietic acid are present in significant amounts in Larix or P. sylvestris bark extracts, respectively. The identified active compounds are gained from a renewable resource potentially available in large quantities at relatively low prices, making them interesting candidates for the development of a plant-derived fungicide active against a key pathogen in agriculture, providing an opportunity to the forest industry to transform low value by-products into high value-added, bioactive extracts. Graphical abstract: Highlights: Plant extracts are effective against Plasmopara viticola infestation. Five lead compounds were isolated. Larixol, lariciresinol, and their acetates from Larix were active. 7α, 15-Dihydroxydehydroabietic acid from Pinus sylvestris was active. Compounds show potential to replace copper products.